2019
DOI: 10.1002/er.4413
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study and mitigation of abnormal behavior of cell voltage in a proton exchange membrane fuel cell stack

Abstract: Summary The aim of this study is to investigate the abnormal behavior of cell voltage in a proton exchange membrane fuel cell stack and a mitigation strategy. The proposed strategy is simple and requires only a three‐way solenoid valve to replace the direct way solenoid valve of the original system. It is applied to a proton exchange membrane fuel cell stack with a dead‐ended anode to verify its validity. The behavior of the cell voltages in the stack is discussed in detail, especially the cell reversal proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Huang, Zhao, and Jian [32] developed an acquisition system using a multichannel system (Smart DAC+GM, Yokogawa Electric Corp., Tokyo, Japan) capable of measuring 40 channels. With this system, they studied the behaviour of fuel cell voltage when starvation occurs, and proposed a technique to resolve this state, using hydrogen at high pressure from an anode outlet, which was effective in improving the performance of the dynamic operation of this system.…”
Section: Previous Workmentioning
confidence: 99%
“…Huang, Zhao, and Jian [32] developed an acquisition system using a multichannel system (Smart DAC+GM, Yokogawa Electric Corp., Tokyo, Japan) capable of measuring 40 channels. With this system, they studied the behaviour of fuel cell voltage when starvation occurs, and proposed a technique to resolve this state, using hydrogen at high pressure from an anode outlet, which was effective in improving the performance of the dynamic operation of this system.…”
Section: Previous Workmentioning
confidence: 99%
“…Chen et al (2016) optimized the opening size of the cathode outlet and found the carbon corrosion of support in both sides becomes less serious with the increase in opening size under the dead-ended anode mode. Lizhong Luo et al (Luo and Jian, 2019) found that the system strategy can help alleviate the fuel cell reversal phenomenon and boost the performance of the stack. By replacing the single-way solenoid valve used in the closed anode with a three-position three-way solenoid valve, the results show that the maximum power of the air-cooler stack increased by 10.96%, which significantly improves the distribution of hydrogen in the anode channel and reduces the voltage fluctuation.…”
Section: Stack and System Strategies Approachesmentioning
confidence: 99%